The rhombic hexecontahedronboron carbide microcrystals – crystal structure analysis. (1st January 2023) - Pavlov, Ivan S.; Ivanova, Anna G.; Filonenko, Vladimir P.; Zibrov, Igor P.; Voloshin, Alexei E.; Zinin, Pavel V.; Vasiliev, Alexander L.
Abstract: One way of boron carbide superhard particles formation is a liquid-phase reaction of M-carborane at high pressure and high temperature. Surprisingly, we found that the particles synthesized in this reaction exhibited the rhombic hexecontahedron morphology with twelve faces formed by five vertices stars ("spikey"). Electron microscopy and X-ray diffraction was applied to the study of the crystal structure of these spectacular particles with twelve 5-fold axis. Results unambiguously demonstrate no quasi-crystalline symptoms and point to the multiple cycling twinning. The decrease of the surface energy during spikey formation at high pressure and high temperature explains the specific shape of the particles. Graphical abstract: Image, graphical abstract